2014 IEEE Symposium on Computational Intelligence in Dynamic and Uncertain Environments (CIDUE) 2014
DOI: 10.1109/cidue.2014.7007864
|View full text |Cite
|
Sign up to set email alerts
|

A framework of scalable dynamic test problems for dynamic multi-objective optimization

Abstract: Dynamic multi-objective optimization has received increasing attention in recent years. One of striking issues in this field is the lack of standard test suites to determine whether an algorithm is capable of solving dynamic multi-objective optimization problems (DMOPs). So far, a large proportion of test functions commonly used in the literature have only two objectives. It is greatly needed to create scalable test problems for developing algorithms and comparing their performance for solving DMOPs. This pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Recently, benchmark generators for continuous dynamic constrained optimization [77,78,26,14] and continuous dynamic multiobjective optimization [25,61,79,80,81,82,83,84,85] are proposed. But, constrained and multi-objective optimization under the discrete space has not attracted much attention yet and deserves future consideration.…”
Section: The Generation Of Dynamicsmentioning
confidence: 99%
“…Recently, benchmark generators for continuous dynamic constrained optimization [77,78,26,14] and continuous dynamic multiobjective optimization [25,61,79,80,81,82,83,84,85] are proposed. But, constrained and multi-objective optimization under the discrete space has not attracted much attention yet and deserves future consideration.…”
Section: The Generation Of Dynamicsmentioning
confidence: 99%
“…According to [31], Jiang and Yang has pointed out that the dynamic nature in the decision variable space can be captured by the function vector, S, in a DMOP model and S(x I ) = S(x II − g(x I )) . Therefore, if we make some modifications of g(x I ), we can obtain various changing patterns of the PS.…”
Section: B Ps Center-based Prediction Methodsmentioning
confidence: 99%
“…Besides, dCOEA uses an additional external population to store useful but outdated archived solutions, hoping to help the evolving population quickly adapt to the new environment by exploiting these history information. It has been shown that dCOEA is very promising for handling dynamic environments [18], [24]. 4) PPS: It is a representative of prediction-based methods that model the movement track of the POF or POS in dynamic environments and then use this model to predict the new location of POS.…”
Section: B Compared Algorithmsmentioning
confidence: 99%